Positive Electrode and Energy Storage Device

The introduction of ionically and nonionically conductive particles with high relative permittivity in the positive electrode mixture layer of lithium-ion secondary batteries addresses the issue of high initial cell resistance and durability-related resistance increases by enhancing dielectric polarization and reducing agglomeration.

JP7649154B2Active Publication Date: 2025-03-19HONDA MOTOR CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021019737
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-02-10
Publication Date
2025-03-19
Estimated Expiration
2041-02-10

AI Technical Summary

Technical Problem

Barium titanate particles with particle sizes of 200 nm or less in lithium-ion secondary batteries have a high specific surface area, leading to agglomeration and reduced contact area with the electrolyte, resulting in insufficient dielectric polarization and increased initial cell resistance.

Method used

A positive electrode comprising a positive electrode current collector and a mixture layer with a positive electrode active material and dielectric particles, where the dielectric particles include ionically conductive and nonionically conductive particles, each with a relative permittivity of 30 or more, to improve dielectric polarization and reduce cell resistance.

Benefits of technology

The use of ionically and nonionically conductive particles in the positive electrode mixture layer enhances dielectric polarization, reduces initial cell resistance, and suppresses corrosion and electrolyte decomposition, thereby maintaining low cell resistance even after durability testing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007649154000001
    Figure 0007649154000001
  • Figure 0007649154000002
    Figure 0007649154000002
  • Figure 0007649154000003
    Figure 0007649154000003
Patent Text Reader

Abstract

To provide a positive electrode capable of making it possible to reduce the cell resistance of a power storage device both initially and after endurance.SOLUTION: The positive electrode has a positive electrode collector and a positive electrode mixture layer. The positive electrode mixture layer includes a positive electrode active material and dielectric particles. The dielectric particles include ion-conductive particles and non-ion-conductive particles.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a positive electrode and an electricity storage device. [Background technology]

[0002] Lithium ion secondary batteries have been widely used as high energy density storage devices. The lithium ion secondary battery has a structure in which, for example, a separator is present between a positive electrode and a negative electrode, and an electrolyte is filled in the lithium ion secondary battery. The positive electrode has a structure in which, for example, a positive electrode mixture layer is formed on a positive electrode current collector.

[0003] Patent Document 1 describes that barium titanate particles having a relative dielectric constant of 500 or more and a particle size of 200 nm or less are dispersed in a positive electrode. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2016-119180 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, since barium titanate particles with a particle size of 200 nm or less are used alone, the barium titanate particles have a high specific surface area and are prone to aggregation. As a result, the contact area with the electrolyte is reduced, and even if the electric field generated inside the lithium ion secondary battery acts on the barium titanate particles, the effect of the dielectric polarization of the barium titanate particles to improve the degree of dissociation of the supporting salt in the electrolyte is insufficient, resulting in an increase in the initial cell resistance.

[0006] On the other hand, there is also a problem that the cell resistance of the lithium ion secondary battery increases after endurance testing because the positive electrode active material corrodes and the electrolyte decomposes in the positive electrode of the lithium ion secondary battery.

[0007] An object of the present invention is to provide a positive electrode capable of reducing the initial and post-endurance cell resistance of an electricity storage device. [Means for solving the problem]

[0008] In one aspect of the present invention, a positive electrode has a positive electrode current collector and a positive electrode mixture layer, the positive electrode mixture layer contains a positive electrode active material and dielectric particles, and the dielectric particles contain ion conductive particles and non-ion conductive particles.

[0009] The positive electrode mixture layer may have a content of the dielectric particles of 0.5% by mass or more and 5% by mass or less.

[0010] The ionically conductive particles and the non-ionically conductive particles may each be oxide particles.

[0011] The ion-conductive particles and the non-ion-conductive particles may each have a relative dielectric constant of 30 or greater.

[0012] The ion conductive particles have a lithium ion conductivity of 1×10 at 25° C. -7 It may be S / cm or more.

[0013] The non-ion conductive particles may have a median diameter of 0.07 μm or more and 0.5 μm or less.

[0014] The ion conductive particles may have a median diameter of 0.4 μm or more and 1.0 μm or less.

[0015] The dielectric particles may have a content of the non-ion conductive particles of 2% by mass or more and 50% by mass or less.

[0016] The dielectric particles may have an ion conductive particle content of 50% by mass or more and 98% by mass or less.

[0017] Another embodiment of the present invention is an energy storage device that includes the above positive electrode, a negative electrode, and an electrolyte solution. Effect of the Invention

[0018] According to the present invention, it is possible to provide a positive electrode capable of reducing the initial and post-endurance cell resistance of an electricity storage device. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] Hereinafter, an embodiment of the present invention will be described.

[0020] <Positive electrode> The positive electrode of the present embodiment includes a positive electrode current collector and a positive electrode mixture layer. The positive electrode mixture layer includes a positive electrode active material and dielectric particles, and the dielectric particles include ion-conductive particles and non-ion-conductive particles.

[0021] In the positive electrode of this embodiment, the positive electrode mixture layer may be formed on one side of the positive electrode current collector, or the positive electrode mixture layer may be formed on both sides of the positive electrode current collector.

[0022] In the positive electrode of this embodiment, since the positive electrode mixture layer contains ion conductive particles and non-ion conductive particles as dielectric particles, the non-ion conductive particles are less likely to aggregate and are more likely to disperse in the positive electrode mixture layer. As a result, when an electric field generated inside the electricity storage device acts on the non-ion conductive particles, the dielectric polarization of the non-ion conductive particles improves the degree of dissociation of the supporting salt in the electrolyte, and the initial cell resistance of the electricity storage device decreases.

[0023] In addition, since the positive electrode mixture layer contains non-ion conductive particles, they have the effect of capturing trace amounts of acid present in the electrolyte and stabilizing the electrolyte through interaction with the electrolyte, thereby suppressing corrosion of the positive electrode active material and decomposition of the electrolyte, and as a result, the cell resistance of the electricity storage device after endurance testing is reduced.

[0024] In order to reduce the initial and post-endurance cell resistance of the electricity storage device, it is preferable to increase the relative dielectric constant of the ion conductive particles and non-ion conductive particles.

[0025] The polarization principle of non-ion conductive particles is that, for example, in the case of BaTiO3, the displacement of the positive and negative charges of each atom when an external electric field is applied is shifted compared to before the external electric field is applied. Even if the non-ion conductive particles are pulverized, the effect on the dielectric polarization is small as long as the crystal structure is maintained. Therefore, when the non-ion conductive particles are pulverized, the surface area increases and the relative dielectric constant increases. Therefore, it is preferable to microparticulate the non-ion conductive particles to have a median diameter of 0.5 μm or less to increase the contact area with the electrolyte.

[0026] On the other hand, when finely divided non-ion conductive particles are used alone, the non-ion conductive particles aggregate with each other, reducing the contact area with the electrolyte, which results in an increase in the initial cell resistance of the electricity storage device.

[0027] On the other hand, the polarization principle of ion conductive particles is believed to be due to the fact that ions diffuse when an external electric field is applied, causing a bias in the ions inside the ion conductive particles. Therefore, when the median diameter of the ion conductive particles is small, the diffusion range of the ions is limited, and the relative dielectric constant of the ion conductive particles is reduced.

[0028] Since the pore diameter of the internal voids of the positive electrode (positive electrode mixture layer) is mainly distributed in the range of 0.02 to 2 μm, it is preferable to use ion-conductive particles and non-ion-conductive particles whose median diameter is within the above range.

[0029] In the positive electrode of this embodiment, the content of the dielectric particles in the positive electrode mixture layer is preferably 0.5% by mass or more and 5% by mass or less, and more preferably 1.0% by mass or more and 2.0% by mass or less. When the content of the dielectric particles in the positive electrode mixture layer is 0.5% by mass or more, the initial cell resistance and the cell resistance after the endurance test of the electricity storage device are reduced, and when it is 5% by mass or less, the energy density of the electricity storage device is improved.

[0030] [Ion conductive particles] The ionically conductive particles may be oxide particles.

[0031] The oxide constituting the oxide particles is, for example, Li 1.3 Al 0.3 Ti 1.7 P3O 12 , Li 0.33 La 0.55 Examples include TiO3, LiNbO3, Li3PO4, etc.

[0032] The relative dielectric constant of the ion conductive particles is preferably equal to or greater than 30, and more preferably equal to or greater than 40. When the relative dielectric constant of the ion conductive particles is equal to or greater than 30, the initial cell resistance of the electricity storage device decreases.

[0033] The lithium ion conductivity of the ion conductive particles at 25°C is 1×10 -7 S / cm or more is preferable, and 1×10 -4 It is more preferable that the lithium ion conductivity of the ion conductive particles at 25° C. is 1×10 S / cm or more. -7 When the capacitance is S / cm or more, the initial cell resistance of the electricity storage device decreases.

[0034] The median diameter of the ion conductive particles is preferably 0.4 μm or more and 1.0 μm or less, and more preferably 0.5 μm or more and 0.8 μm or less. When the median diameter of the ion conductive particles is 0.4 μm or more and 1.0 μm or less, the initial cell resistance of the electricity storage device decreases.

[0035] The content of the ion conductive particles in the dielectric particles is preferably 50% by mass or more and 98% by mass or less, and more preferably 60% by mass or more and 70% by mass or less. When the content of the ion conductive particles in the dielectric particles is 50% by mass or more, the initial cell resistance of the electricity storage device decreases, and when it is 98% by mass or less, the cell resistance after endurance testing of the electricity storage device decreases.

[0036] [Non-ion conductive particles] The non-ionically conductive particles may be oxide particles.

[0037] The oxide constituting the oxide particles is, for example, BaTi 1-x Zr x O3(0≦X≦0.5), SrBi2Ta2O9, (K 1-x Na x )NbO3(0≦X≦1), BiFeO 3、 CaCu3Ti4O 12 etc.

[0038] The non-ion conductive particles preferably have a relative dielectric constant of at least 30, and more preferably at least 40. When the non-ion conductive particles have a relative dielectric constant of at least 30, the cell resistance of the electricity storage device after endurance testing decreases.

[0039] The median diameter of the non-ion conductive particles is preferably 0.07 μm or more and 0.5 μm or less, and more preferably 0.1 μm or more and 0.5 μm or less. When the median diameter of the non-ion conductive particles is 0.07 μm or more and 0.5 μm or less, the cell resistance of the electricity storage device after endurance testing decreases.

[0040] The content of the non-ion conductive particles in the dielectric particles is preferably 2% by mass or more and 50% by mass or less, and more preferably 30% by mass or more and 40% by mass or less. When the content of the non-ion conductive particles in the dielectric particles is 2% by mass or more, the cell resistance of the electricity storage device after endurance testing decreases, and when it is 50% by mass or less, the initial cell resistance of the electricity storage device decreases.

[0041] [Positive electrode mixture layer] The positive electrode mixture layer contains a positive electrode active material and dielectric particles, and may further contain other components.

[0042] Examples of the other components include a solid electrolyte, a conductive assistant, and a binder.

[0043] The positive electrode active material is not particularly limited as long as it is capable of absorbing and releasing lithium ions. For example, LiCoO2, Li(Ni 5 / 10 Co 2 / 10 Mn 3 / 10 )O 2、 Li(Ni) 6 / 10 Co 2 / 10 Mn 2 / 10 )O 2、 Li(Ni) 8 / 10 Co 1 / 10 Mn 1 / 10 )O 2、 Li(Ni) 0.8 Co 0.15 Al 0.05 )O 2、 Li(Ni) 1 / 6 Co 4 / 6 Mn 1 / 6 )O 2、 Li(Ni) 1 / 3 Co 1 / 3 Mn 1 / 3 )O 2、 Examples include LiCoO4, LiMn2O4, LiNiO2, LiFePO4, lithium sulfide, and sulfur.

[0044] [Positive electrode current collector] The positive electrode current collector is not particularly limited, but examples thereof include metal foil.

[0045] The metal that constitutes the metal foil may be, for example, aluminum.

[0046] <Manufacturing method of positive electrode> The method for producing the positive electrode of the present embodiment is not particularly limited, and a typical method in this technical field can be applied. For example, a method of applying a positive electrode mixture layer paste containing a positive electrode active material and dielectric particles onto a positive electrode current collector and then drying the applied paste can be mentioned.

[0047] After the positive electrode mixture layer is formed on the positive electrode current collector, a method generally used in the art can be applied. For example, the positive electrode current collector on which the positive electrode mixture layer is formed is pressed to obtain a positive electrode. At this time, the density of the positive electrode can be adjusted by pressing.

[0048] <Electricity storage device> The electricity storage device of this embodiment includes the positive electrode of this embodiment, a negative electrode, and an electrolyte solution.

[0049] Examples of the power storage device include secondary batteries such as lithium ion secondary batteries, and capacitors.

[0050] The negative electrode is not particularly limited, and any known negative electrode that can be applied to an electricity storage device can be used.

[0051] The electrolyte is not particularly limited, and any known electrolyte that can be applied to an electricity storage device can be used.

[0052] [Lithium-ion secondary battery] The lithium ion secondary battery of this embodiment includes the positive electrode of this embodiment, a negative electrode, an electrolyte, and a separator located between the positive electrode and the negative electrode.

[0053] In the lithium ion secondary battery of this embodiment, two types of materials are selected from materials capable of forming electrodes, and the charge / discharge potentials of the two types of materials are compared. The material exhibiting a more noble potential is applied to the positive electrode, and the material exhibiting a more base potential is applied to the negative electrode, thereby making it possible to form any battery.

[0054] The separator is not particularly limited, and any known separator that can be applied to lithium ion secondary batteries can be used. EXAMPLES

[0055] Examples of the present invention will be described below, but the present invention is not limited to these examples.

[0056] [Dielectric particles] After obtaining the dielectric particles from Toshima Manufacturing Co., Ltd., the dielectric particles that required adjustment of the median diameter were pulverized by a ball mill using IPA.

[0057] Table 1 shows the properties of the ion conductive particles.

[0058] [Table 1]

[0059] Table 2 shows the properties of the non-ion conductive particles.

[0060] [Table 2]

[0061] [Method for measuring the dielectric constant of powder] The powder was introduced into a tablet press with a diameter (R) of 38 mm for measurement, and then compressed to a thickness (d) of 1 to 2 mm using a hydraulic press to form a green compact. powder The powder compact was molded so that the mass density of the powder compact / the true specific gravity of the powder x 100 was 40% or more. Next, the capacitance C of the powder compact at 25°C and 1 kHz was measured by the automatic balancing bridge method using an LCR meter. total The dielectric constant ε of the green compact was measured. total Next, the dielectric constant of vacuum, ε0, was calculated as 8.854×10 -12 , the relative dielectric constant of air ε air is set to 1, and the relative dielectric constant ε of the powder (actual volume portion) is calculated using the following equations (1) to (3). power was calculated. Contact area between powder compact and electrode A = (R / 2) 2 ×π (1) C total =ε total ×ε0×(A / d) (2) ε total =ε powder ×D powder +ε air ×(1-D powder ) · · · (3)

[0062] [Method for measuring Li-ion conductivity] Au was sputtered onto both sides of the powder compact to prepare electrodes. Using the prepared electrodes, an AC two-terminal method was used to measure the frequency of 1 to 10 Hz at an applied voltage of 50 mV and a temperature of 25°C. 6 The Li-ion conductivity was measured in the range of 100 Hz. At this time, the Li-ion conductivity k was calculated from the resistance value Ri by finding the real number at the point where the imaginary component of the impedance becomes 0. The measuring equipment used was a solatron 1260 / 1287. The Li-ion conductivity k is expressed by the following formula (4), where A' is the area of ​​Au and l is the thickness of the green compact. k = l / (Ri × A') (4)

[0063] [Powder median diameter (D 50 ) Measurement method The particle size distribution of the powder was measured using a particle size distribution measuring device MT3000II (manufactured by Microtrac). At this time, water was used as a solvent, the refractive index was set to 1.81, and the particle size value at a cumulative percentage of 50 was taken as the median diameter.

[0064] <Examples 1 to 8 and Comparative Examples 1 to 3> [Preparation of positive electrode] The dielectric particles, acetylene black (AB) as a conductive assistant, and polyvinylidene fluoride (PVDF) as a binder were premixed with N-methyl-2-pyrrolidone (NMP) as a dispersion medium, and then wet-mixed using a centrifugal mixer to obtain a premixed slurry. 0.6 Co 0.2 Mn 0.2 After mixing O2 (NCM622) and the premixed slurry, a dispersion process was performed using a planetary mixer to obtain a positive electrode mixture layer paste. The mass ratio of each component in the positive electrode mixture layer paste is shown in Table 3. Here, NCM622 has a median diameter of 12 μm.

[0065] The positive electrode composite layer paste was applied to an aluminum foil as a positive electrode current collector, and then dried. Next, the dried positive electrode current collector was pressed by a roll press, and then dried in a vacuum at 120°C to form a positive electrode composite layer, thereby obtaining a positive electrode plate. The obtained positive electrode plate was punched out to a size of 30 mm x 40 mm to obtain a positive electrode.

[0066] [Preparation of negative electrode] An aqueous solution of carboxymethyl cellulose (CMC) as a binder and acetylene black (AB) as a conductive assistant were premixed using a planetary mixer. Next, natural graphite (NG) as a negative electrode active material was mixed, and then premixed using a planetary mixer. Next, water as a dispersion medium and styrene butadiene rubber (SBR) as a binder were added, and then a dispersion process was performed using a planetary mixer to obtain a negative electrode mixture layer paste. The mass ratio of each component in the negative electrode mixture layer paste was NG:AB:CMC:SBR=96.5:1.0:1.0:1.5. NG has a median diameter of 12 μm.

[0067] The negative electrode composite layer paste was applied to a copper foil as a negative electrode current collector, and then dried. Next, the dried negative electrode current collector was pressed by a roll press, and then dried in a vacuum at 130°C to form a negative electrode composite layer, thereby obtaining a negative electrode plate. The obtained negative electrode plate was punched out to a size of 34 mm x 44 mm to obtain a negative electrode.

[0068] [Preparation of lithium-ion secondary batteries] Aluminum laminate for secondary batteries (manufactured by Dai Nippon Printing) was heat-sealed and processed into a bag to obtain a container. Next, a laminate in which a separator was sandwiched between a positive electrode and a negative electrode was introduced into the inside of the container, and then an electrolyte was poured into the interface of each electrode. Next, the container was reduced in pressure to -95 kPa and sealed to produce a lithium-ion secondary battery. As the separator, a polyethylene microporous film coated on one side with alumina particles at a thickness of about 5 μm was used. As the electrolyte, a solution in which LiPF6 was dissolved as an electrolyte salt at a concentration of 1.2 mol / L in a mixed solvent of ethylene carbonate, ethyl methyl carbonate, and dimethyl carbonate in a volume ratio of 30:30:40 was used.

[0069] <Evaluation of initial performance of lithium-ion secondary batteries> The lithium ion secondary batteries of Examples 1 to 8 and Comparative Examples 1 to 3 were evaluated for initial performance as follows.

[0070] [Discharge capacity] The lithium ion secondary battery was left at the measurement temperature (25°C) for 1 hour, and then constant current charging was performed at 8.4mA up to 4.2V, followed by constant voltage charging at a voltage of 4.2V for 1 hour. Next, the lithium ion secondary battery was left for 30 minutes, and then constant current discharging was performed at a current value of 8.4mA down to 2.5V. Next, the above operation was repeated 5 times, and the discharge capacity at the 5th discharge was taken as the discharge capacity (mAh). The current value at which the discharge could be completed in 1 hour for the obtained discharge capacity was taken as 1C.

[0071] [Cell resistance] The lithium ion secondary battery after measuring the discharge capacity was left at the measurement temperature (25°C) for 1 hour, and then constant current charging was performed at a charge rate of 0.2C, and the charge level (SOC (State of Charge)) was adjusted to 50% and left for 10 minutes. Next, pulse discharge was performed at a discharge rate of 0.5C for 10 seconds, and the voltage when discharged for 10 seconds was measured. Then, the horizontal axis was the current value and the vertical axis was the voltage, and the voltage when discharged for 10 seconds was plotted against the discharge rate of 0.5C. Next, the lithium ion secondary battery was left for 10 minutes, and then supplementary charging was performed to return the SOC to 50%, and the lithium ion secondary battery was left for 10 minutes. Next, the above operation was performed at each discharge rate of 1.0C, 1.5C, 2.0C, 2.5C, and 3.0C, and the voltage when discharged for 10 seconds was plotted against each discharge rate. Then, the slope of the approximation line obtained by the least squares method from each plot was taken as the cell resistance (mΩ).

[0072] <Evaluation of endurance performance of lithium-ion secondary batteries> The lithium ion secondary batteries of Examples 1 to 8 and Comparative Examples 1 to 3 were subjected to the following evaluation of post-durability performance.

[0073] [Discharge capacity] In a thermostatic chamber at 45°C, the lithium-ion secondary battery was charged at a constant current of 1C to 4.2V, and then discharged at a constant current of 2C to 2.5V, with this operation being considered as one cycle. The above operation was repeated 500 cycles. Next, the temperature of the thermostatic chamber was changed to 25°C, and the lithium-ion secondary battery was left for 24 hours. Next, a constant current charge was performed at a charge rate of 0.2C to 4.2V, followed by a constant voltage charge at a voltage of 4.2V for 1 hour. Next, the lithium-ion secondary battery was left for 30 minutes, and then a constant current discharge was performed at a discharge rate of 0.2C to 2.5V, and the discharge capacity (mAh) was measured.

[0074] [Cell resistance] After measuring the discharge capacity, the lithium ion secondary battery was adjusted to a charge level (SOC (State of Charge)) of 50% in the same manner as in measuring the initial performance, and then the cell resistance (mΩ) was determined.

[0075] [Capacity maintenance rate] The ratio of the discharge capacity after endurance testing to the discharge capacity at the initial stage was calculated and defined as the capacity retention rate (%).

[0076] [Resistance change rate] The ratio of the cell resistance after endurance testing to the cell resistance at the initial stage was calculated and defined as the resistance change rate (%).

[0077] Table 3 shows the evaluation results of the initial performance and post-durability performance of lithium-ion secondary batteries.

[0078] [Table 3]

[0079] It can be seen from Table 3 that the lithium ion secondary batteries of Examples 1 to 8 had low initial and post-endurance cell resistances.

[0080] In contrast, the lithium ion secondary battery of Comparative Example 1 has a high cell resistance after endurance testing because the positive electrode mixture layer does not contain dielectric particles. Also, the lithium ion secondary battery of Comparative Example 2 has a high cell resistance after endurance testing because the positive electrode mixture layer does not contain non-ion conductive particles. Furthermore, the lithium ion secondary battery of Comparative Example 3 has a high initial cell resistance because it does not contain ion conductive particles.

Claims

1. A positive electrode current collector and a positive electrode mixture layer, the positive electrode mixture layer includes a positive electrode active material and dielectric particles, and a content of the dielectric particles is 1% by mass or more and 5% by mass or less; the dielectric particles include ion-conductive particles and non-ion-conductive particles, the content of the non-ion-conductive particles is 2% by mass or more and 50% by mass or less, and the content of the ion-conductive particles is 50% by mass or more and 98% by mass or less; the ion conductive particles are Li0.33La0.55TiO3 particles, LiNbO3 particles, or Li3PO4 particles, and have a relative dielectric constant of 30 or more; A positive electrode, wherein the non-ion conductive particles are BaTi 1-x Zr x O 3 (0≦x≦0.5) particles and have a relative dielectric constant of 30 or more.

2. The positive electrode according to claim 1 , wherein the non-ion conductive particles have a median diameter of 0.07 μm or more and 0.5 μm or less.

3. The positive electrode according to claim 1 or 2, wherein the ion conductive particles have a median diameter of 0.4 μm or more and 1.0 μm or less.

4. An electricity storage device comprising: the positive electrode according to claim 1 ; a negative electrode; and an electrolyte solution.

Citation Information

Patent Citations

  • Non-aqueous lithium secondary battery

    JP2016119180A

  • Electrode, secondary battery, battery pack and vehicle

    JP2019169252A

  • All-solid ion secondary cell

    WO2014132320A1

  • Electrolytic solution absorbing particles, self-supporting sheet, lithium-ion secondary battery electrode, separator, and lithium-ion secondary battery

    WO2020245911A1